Developmental, Dietary, and Geographical Impacts on Gut Microbiota of Red Swamp Crayfish (Procambarus clarkii) - Zhang, Zhenting; Liu, Jiali; Jin, Xuexia; Liu, Chao; Fan, Chenwei; Guo, Li; Liang, Yunxiang; Zheng, Jinshui; Peng, Nan (Microorganisms (Basel), 2020)
Red swamp crayfish (Procambarus clarkii) breeding is an important economic mainstay in Hubei province, China. However, information on the gut microbiota of the red swamp crayfish is limited. To address this issue, the effect of developmental stage, diet (fermented or non-fermented feed), and geographical location on the gut microbiota composition in the crayfish was studied via high-throughput 16S rRNA gene sequencing. The results revealed that the dominant phyla in the gut of the crayfish were Proteobacteria, Bacteroidetes,Firmicutes, Tenericutes, and RsaHF231. The alpha diversity showed a declining trend during development, and a highly comparable gut microbiota clustering was identified in a development-dependent manner. The results also revealed that development, followed by diet, is a better key driver for crayfish gut microbiota patterns than geographical location. Notably, the relative abundance of Bacteroidetes was significantly higher in the gut of the crayfish fed with fermented feed than those fed with non-fermented feed, suggesting the fermented feed can be important for the functions (e.g., polysaccharide degradation) of the gut microbiota. In summary, our results revealed the factors shaping gut microbiota of the crayfish and the importance of the fermented feed in crayfish breeding.